التربية على القيم كمرجعية أساسية في بناء المناهج التعليمية - غانم, إبتسام (جامعة الوادي - University of Eloued, 2021)
هدفت الورقة البحثية الراهنة مقاربة موضوع التربية على القيم، من خلال تأسيس نظري ومفهومي للقيم، إضافة إلى التعرض إلى المكانة التي تحظى بها القيم في المناهج التعليمية الجزائرية، باعتبارها عنصرا فعالا في امتلاك المتعلمين قيما ذات مرجعية مشتركة وأصيلة، كذلك التطرق للأهمية التي يمكن رصدها عبر استثمار التربية على القيم في المناهج التعليمية، انطلاقا من مبدأ التكامل بين مختلف المواد الدراسية المكونة للمنهاج التعليمي في بناء منظومة القيم لدى المتعلمين، وكذلك من خلال تكوين شخصية المتعلم السليمة والمتوازنة، والمتسلح إلى جانب ذلك بكل المهارات الحياتية اللازمة. وقد اعتمدنا في ذلك على المنهج التحليلي الاستنباطي، من خلال تحليل ما ورد من معطيات حول هذا الموضوع، حيث توصلنا إلى أن منظومة القيم هي التي تحصن المجتمع من أي انحراف فكري أو سلوكي، وعليه فإن المدرسة بمنظومتها التربوية وقيمها الخالدة مدعوة لتعزيز التربية على القيم، باعتبارها سلاحا تربويا يفرض ذاته بقوة على المجتمعات المعاصرة التي تعيش جملة من التغييرات والتجديدات، خصوصا أن الواقع المعاش يجعل من المؤسسات التعليمية هي الفضاء الأمثل لنشر القيم وتصحيحها وترسيخها عبر المناهج والبرامج التعليمية. الكلمات المفتاحية: قيم؛ تربية؛ تربية على القيم؛ مناهج تعليمية؛ مرجعية؛ بناء. Abstract The current research paper aimed to approach the subject of education on values, through the theoretical and conceptual establishment of values, as well as to reveal the position of values in the Algerian educational curricula, as an effective element in the learners' possession of values of common and original reference, not to mention addressing the importance that can be monitored through Investing in education on values in educational curricula, which will be based on the principle of complementarity between the various academic subjects that make up the educational curriculum in building the value system of learners, as well as through the formation of the learner's personality, sound and balance, and in addition to that, armed with all the necessary life skills. We have relied in this on the deductive analytical approach, by analyzing the data received on this topic, as we have concluded that the value system is the one that protects society from any intellectual or behavioral deviation, and accordingly the school, with its educational system and its eternal values, is responsible for the promotion of educational values as an educational weapon that imposes it self strongly and effectively on contemporary societies that are experiencing a series of changes and innovations, especially since the lived reality makes educational institutions the ideal space for disseminating, correcting and consolidating values through educational curricula and programs.
Values education as a basic reference in building educational curriculaValues education as a basic reference in building educational curricula
مقال
Keywords: قيم تربية ، تربية على القيم، مناهج تعليمية ، مرجعية بناء: Values; Education; Values education; Educational curricula; Reference; Building.